2010
DOI: 10.4111/kju.2010.51.4.260
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing Acute Pyelonephritis with CT,99mTc-DMSA SPECT, and Doppler Ultrasound: A Comparative Study

Abstract: PurposeWith growing interest in early imaging, the aim of our study was to define the most practical modality for routine clinical use for the diagnosis of acute pyelonephritis (APN). We compared the sensitivity of enhanced computerized tomography (CT), dimercaptosuccinic acid (DMSA) scintigraphy, and Doppler ultrasonography (DUS) by using clinical findings as the standard of reference.Materials and MethodsA total of 207 APN patients (191 women, 16 men; mean age, 49.4 years; range, 17-88 years) were enrolled i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 24 publications
0
24
0
1
Order By: Relevance
“…Shen and Brown stated that early imaging is cost-effective and advocate imaging in people who are going to be hospitalized by APN (14,15). Yoo et al (14) reported that there are clinically significant findings in 16% of the patients. MDCT is important for the detection of abscess and APN.…”
Section: Urinary Tract Infectionsmentioning
confidence: 99%
“…Shen and Brown stated that early imaging is cost-effective and advocate imaging in people who are going to be hospitalized by APN (14,15). Yoo et al (14) reported that there are clinically significant findings in 16% of the patients. MDCT is important for the detection of abscess and APN.…”
Section: Urinary Tract Infectionsmentioning
confidence: 99%
“…Kairysis inkstas padidėjęs su aplink pastebima skysčio sankaupa, viršutiniame poliuje hiperintensinė, neaiškių ribų zona; MRT T2 vaizdai scintigrafija negali atskirti ūminio pažeidimo nuo esančių randinių pakitimų, teigiami radiniai nebūtinai rodo ūmi-nį pielonefritą, galutinę diagnozę galima nustatyti tik po 6 mėnesių stebėjimo. Jie padarė išvadą, kad šiuo metu KT yra tinkamiausias tyrimas kasdienėje klinikinėje praktikoje diagnozuojant ūminį pielonefritą [13]. 6 pav.…”
Section: Vaizdiniai Tyrimaiunclassified
“…Contrast-enhanced CT is the imaging study of choice for detection of acute pyelonephritis, and has a greater sensitivity as compared to ultrasound. 17 Common CT findings are poorly defined wedge-shaped lesions that have decreased attenuation. Often this radiates from the papilla in the medulla to the cortical surface.…”
Section: Case #3: Uti and Acute Pyelonephritismentioning
confidence: 99%
“…Also, bands of hyperattenuation and hypoattenuation oriented in parallel of the tubules and collecting ducts can be seen. 17 Treatment of pyelonephritis includes initial empirical therapy, which should be started while awaiting a urine culture and susceptibility test and should be tailored based on the microorganism. 18 In general, oral ciprofloxacin 500 mg twice daily for 7 days is the choice of antibiotic for patients not requiring hospitalization.…”
Section: Case #3: Uti and Acute Pyelonephritismentioning
confidence: 99%